Kuwait: Islamic banking for a consumer society - Wilson, Rodney 1946- (1990)
The Kuwait Finance House was established in 1977. It was set up as an Islamic investment bank, operating under a special government decree which recognized the Islamic nature of the institution. The article reviews its experience, examining its activities, performance, profitability, liquidity positions, and returns to depositors and investors. (DÜI-Ott)
Keywords: Bank; Islam; Wirtschaftsordnung; Islamische Bank; Kuwait -- Kuwait Finance House (Safat) -- Bank -- Islam -- Islamische Wirtschaftsordnung -- Islamic Finance; Kuwait